2018
DOI: 10.7150/thno.23852
|View full text |Cite
|
Sign up to set email alerts
|

High-Discrimination Factor Nanosensor Based on Tetrahedral DNA Nanostructures and Gold Nanoparticles for Detection of MiRNA-21 in Live Cells

Abstract: While detection of microRNA with or without signal amplification is highly informative, nanosensors with high specificity for cell-specific RNA detection are rare.Methods: In this study, a tetrahedral DNA nanostructure (TDN) with a specific function was combined with gold nanoparticles (Au-NP) possessing fluorescence quenching effects and a large surface area to fabricate a fluorescence resonance energy transfer based nanosensor (Au-TDNN). The presence of miR-21 (target) can separate the fluorescent dye-labele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This process releases the target microRNA to enable several reaction cycles resulting in more fluorophore release. Xie and co-workers designed fluorescent DNA probes attached to gold nanoparticles, additionally using DNA tetrahedra to control the probe surface density (116). Target microRNA binds and releases the fluorophore-containing strand in the duplex, releasing it from the quenching nanoparticle and increasing fluorescence.…”
Section: Dna-based Nanostructures For Micro Rna Detectionmentioning
confidence: 99%
“…This process releases the target microRNA to enable several reaction cycles resulting in more fluorophore release. Xie and co-workers designed fluorescent DNA probes attached to gold nanoparticles, additionally using DNA tetrahedra to control the probe surface density (116). Target microRNA binds and releases the fluorophore-containing strand in the duplex, releasing it from the quenching nanoparticle and increasing fluorescence.…”
Section: Dna-based Nanostructures For Micro Rna Detectionmentioning
confidence: 99%
“… 6 Our team previously presented real-time detection of microRNA-21 (miR-21) in HepG2 cells, by utilizing a 6-carboxy-fluorescein (6-FAM) labeled DNA tetrahedral modified AuNPs fluorescent probe. 7 However, ultraviolet (UV) or visible light-excited fluorescence signals are confronted with drawbacks like slight penetration depth, photodamage and interference of auto-fluorescence. Considerable research shows that near-infrared nanomaterials excited by long-wavelength light have obvious advantages in bioanalysis.…”
Section: Introductionmentioning
confidence: 99%
“…33−39 In particular, many studies reported that a tetrahedral framework nucleic acid (tFNA) could serve as a promising DNA nanocarrier for many antitumor drugs, owing to its high biocompatibility and biosecurity. 40−42 For example, tFNA was reported to effectively deliver paclitaxel or doxorubicin to cancer cells for reversing drug resistance, 41,42 small interfering RNAs (siRNAs) have been modified into tFNA for targeted drug delivery, 43,44 and tFNA could deliver antisense peptide nucleic acids to inhibit methicillin-resistant Staphylococcus aureus. 45 Moreover, the production and storage of tFNA are not complicated, and they can be quickly degraded in lysosomes by cells.…”
mentioning
confidence: 99%
“…DNA origami is an emerging field of DNA-based nanotechnology, and intelligent DNA nanorobots show great promise in working as a drug delivery system in healthcare. Different DNA-based nanorobots have been developed as affordable and facile therapeutic drugs. In particular, many studies reported that a tetrahedral framework nucleic acid (tFNA) could serve as a promising DNA nanocarrier for many antitumor drugs, owing to its high biocompatibility and biosecurity. For example, tFNA was reported to effectively deliver paclitaxel or doxorubicin to cancer cells for reversing drug resistance, , small interfering RNAs (siRNAs) have been modified into tFNA for targeted drug delivery, , and tFNA could deliver antisense peptide nucleic acids to inhibit methicillin-resistant Staphylococcus aureus . Moreover, the production and storage of tFNA are not complicated, and they can be quickly degraded in lysosomes by cells. , Since both free HApt and tFNA can be diverted into lysosomes, we hypothesized that combining the HApt and tFNA as a novel DNA nanorobot (namely, HApt-tFNA) would be an effective strategy to improve its delivery and therapeutic efficacy in treating HER2-positive breast cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation